2003
DOI: 10.1136/jnnp.74.5.608
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of neurological involvement in Behcet's disease: a prospective study from Iraq

Abstract: Objectives: To determine the prevalence of neurological involvement in Behcet's disease in a prospective study, and to describe the clinical patterns of neurological presentation in this disease in patients attending a multidisciplinary clinic in Baghdad. Methods: All patients attending the clinic who fulfilled the international study group criteria for the diagnosis of Behcet's disease were studied during a two year period starting in April 1999. Patients were assessed neurologically by a neuro-Behcetologist.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
71
5
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 19 publications
11
71
5
10
Order By: Relevance
“…Previous studies found similar results, with a prevalence of CVT from 10 -12% among patients with neuro-BD (8,19). Conflicting results have been reported in other studies (20,21). In a prospective study of 323 consecutive patients with BD, only 2 cases of CVT were found among 17 patients with neurologic symptoms (4).…”
Section: Discussionmentioning
confidence: 38%
“…Previous studies found similar results, with a prevalence of CVT from 10 -12% among patients with neuro-BD (8,19). Conflicting results have been reported in other studies (20,21). In a prospective study of 323 consecutive patients with BD, only 2 cases of CVT were found among 17 patients with neurologic symptoms (4).…”
Section: Discussionmentioning
confidence: 38%
“…However, in some studies, up to 20 % of patients can present with a combination of the 2 forms [143,144].…”
Section: Behçet's Disease (Bd)mentioning
confidence: 99%
“…Ayrıca var olan nörolojik semptomların başka bilinen bir sistemik veya nörolojik hastalıkla açıklanamaması ve bunlara pozitif nörolojik muayene, NBH düşündürecek MRG veya NBH ile uyumlu BOS incelemelerinden en az birinin eşlik etmesi gerekmektedir (7). Irak'ta BH olan hastalarla yapılan bir çalışmada, hastaların %14.3'ünde nörolojik tutulumun eşlik ettiğini ve bunlarda tanının, klinik bulgulara BOS veya MRG bulgularından birinin eşlik etmesiyle kesinleştirildiği belirtilmiştir (11). Literatürde psikoz atağı sonrasında çekilen MRG bulgularından tanı konulan bir NBH olgusu vardır (12).…”
Section: İrdelemeunclassified